Hadist Ibnu Abbas tentang Menjaga Lima Perkara Sebelum Datang Lima Perkara yang Lain (Al-Hakim) - Hendi Supandi; Istikhori Istikhori; Toha Suryana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Hadith narrated by Ibn Abbas r.a. regarding guarding five things before the other five things come, provides a moral message that is very relevant in the daily lives of Muslims. This hadith teaches people to take advantage of youth, health, wealth, free time and life before things come that can hinder their use. This journal aims to analyze and examine the meaning and relevance of this hadith in contemporary life. Through a hadith analysis approach, this journal shows that the messages contained in this hadith can be applied in various aspects of life, from time management to health and wealth. Apart from that, this journal also discusses the asbabul wurud of this hadith, its validity status, as well as the tarbiyah aspects contained in it